A Cross‐Lagged Panel Study of Dissociation and Posttraumatic Stress in a Treatment‐Seeking Sample of Survivors of Childhood Sexual Abuse. Issue 10 (10th January 2017) - Murphy, Siobhan; Elklit, Ask; Murphy, Jamie; Hyland, Philip; Shevlin, Mark
Abstract : Objective: The current prospective study assessed the temporal relations between dissociation and posttraumatic stress (PTS) in a sample of treatment‐seeking female survivors of childhood sexual abuse. PTS refers to symptoms associated with posttraumatic stress disorder (PTSD) in the absence of a clinical diagnosis of PTSD. Method: Initial assessment was on average 23 years after the onset of abuse (N = 405), and participants were followed‐up after 6 months (N = 245) and 12 months (N = 119). Results: Findings indicated that dissociative experiences and PTS were highly correlated within each wave of data collection. Cross‐lagged panel analysis revealed that at each assessment period dissociative symptoms and PTS levels, respectively, were primarily explained by scores on the same variable at the previous assessment period. Although further reciprocal relations between dissociation and PTS were evident, these associations were relatively weak in magnitude. Conclusion: Current results provide important insights into the temporal relations between dissociative symptoms and PTS. The high correlations between dissociative experiences and PTS several years after trauma exposure have important clinical implications that may affect their treatment and trauma recovery.